2022
DOI: 10.2147/idr.s380952
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B Virus, Hepatitis C Virus, Syphilis and Associated Factors Among Female Sex Workers in Gondar Town, Northwest Ethiopia

Abstract: Background Sexually transmitted infections (STIs) are a public health problem worldwide. Hepatitis B virus infection (HBV), hepatitis C virus infection (HCV), and syphilis are among the STIs. Female sex workers (FSWs) continue to be a high-risk group for STIs due to a variety of factors, including exposure to unsafe sexual practices. Therefore, this study determines the seroprevalence of HBV, HCV, Treponema palladium , and associated factors among FSWs in Gondar town, No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…There were no data indicating a national prevalence of HCV among FSWS, however the report from Dessie City, Northeast Ethiopia and Gondar Town, Northwest Ethiopia indicates the prevalence of HCV among FSWs 0.6% and 6.7% respectively [12]. The lack of access to regular screening of STIs among FSWs contributes a lot to the disease's transmission in resourcelimited countries, including Ethiopia and the national study on HCV will be a pre requisite for this study groups [18].…”
Section: Introductionmentioning
confidence: 96%
“…There were no data indicating a national prevalence of HCV among FSWS, however the report from Dessie City, Northeast Ethiopia and Gondar Town, Northwest Ethiopia indicates the prevalence of HCV among FSWs 0.6% and 6.7% respectively [12]. The lack of access to regular screening of STIs among FSWs contributes a lot to the disease's transmission in resourcelimited countries, including Ethiopia and the national study on HCV will be a pre requisite for this study groups [18].…”
Section: Introductionmentioning
confidence: 96%
“…health care and sex workers). [9][10][11] The natural history of HCV infection in women is characterized by a higher rate of spontaneous elimination of HCV viremia compared to men and a slower progression to cirrhosis and HCC in the premenopausal period. 12 These percentages level off and even reverse in postmenopausal women when the frequency of HCV infections and progression to unfavourable clinical consequences is significantly higher in women.…”
Section: Introductionmentioning
confidence: 99%
“…drug use, sexual behaviour, tattoos) and typically female professions associated with increased exposure to infection (e.g. health care and sex workers) 9–11 . The natural history of HCV infection in women is characterized by a higher rate of spontaneous elimination of HCV viremia compared to men and a slower progression to cirrhosis and HCC in the premenopausal period 12 .…”
Section: Introductionmentioning
confidence: 99%
“…14 Furthermore, the military is frequently mobile from place to place for different professional reasons and stays longer without their family, which may cause them to have multiple sex partners and increase their exposure to different sexually transmitted infections (STIs). 16 Several studies have reported the prevalence of HBV and HCV infections among different segments of the population in the study area [17][18][19][20][21][22][23][24] and there is a single report of armed forces in Bahir Dar, Amhara Regional State of Ethiopia. 16 No data were described the prevalence of viral hepatitis among military personnel in the study area.…”
Section: Introductionmentioning
confidence: 99%